2022
DOI: 10.1093/ehjci/jeac240
|View full text |Cite
|
Sign up to set email alerts
|

Unfavourable outcomes in patients with heart failure with higher preserved left ventricular ejection fraction

Abstract: Aims Newly introduced drugs for heart failure (HF) have been reported to improve the prognosis of HF with preserved ejection fraction (HFpEF) in the lower range of left ventricular ejection fraction (LVEF). We hypothesized that a higher LVEF is related to an unfavourable prognosis in patients with HFpEF. Methods and results We tested this hypothesis by analysing the data from a prospective multicentre cohort study in 255 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Recently, we have reported that a higher EF of ≥58% is independently related to a poor prognosis in patients with HFpEF. 2 Many studies support our findings, showing a U-shaped relationship between EF and mortality, with the nadir at an EF of 60% to 65%. 3 Surprisingly, patients with an EF of ≥70% (supernormal EF) had a similar adjusted mortality rate as patients with an EF of 35% to 40%.…”
supporting
confidence: 87%
“…Recently, we have reported that a higher EF of ≥58% is independently related to a poor prognosis in patients with HFpEF. 2 Many studies support our findings, showing a U-shaped relationship between EF and mortality, with the nadir at an EF of 60% to 65%. 3 Surprisingly, patients with an EF of ≥70% (supernormal EF) had a similar adjusted mortality rate as patients with an EF of 35% to 40%.…”
supporting
confidence: 87%
“…Microvascular endothelial dysfunction in the heart of patients with HFpEF can cause a cascade of events, resulting in concentric LV remodeling, diastolic dysfunction, and higher end-systolic volume and pressure [1], reflected by non-invasive echocardiography markers such as decreased e' and elevated E/e' [19]. The degree of impairment in these echocardiography markers is associated with a worse prognosis [20,21]. These impairments can be improved, thereby partially restoring exercise capacity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and clinical trials have shown that inhibition of the RAAS can improve cardiac diastolic function and downregulate these harmful processes [27], but the clinical benefits of neurohormone antagonists in HFpEF patients are uncertain. In HFpEF patients, the use of ACE inhibitors/Ang II type 1 receptor blockers is related to the improvement of prognosis, especially in terms of readmission due to HF [28]. In this study, we used DSS rats to induce an HFpEF model, intervened with CANA and IRB administration, and studied the mechanism of action of CANA.…”
Section: Discussionmentioning
confidence: 99%